2020
DOI: 10.3390/sports8100131
|View full text |Cite
|
Sign up to set email alerts
|

Role of a Ketogenic Diet on Body Composition, Physical Health, Psychosocial Well-Being and Sports Performance in Athletes: A Scoping Review

Abstract: Background: Recently, a focus has been placed on investigating the potential benefits of adherence to a ketogenic diet in enhancing body composition, physical health, psychological well-being, and performance of athletes from various sporting disciplines. As the available research is yet to be collated and analyzed in a single review, this scoping review aims to analyze and draw conclusions from the available literature that exists on the efficacy of a ketogenic diet among athletic populations. Methods: Severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…While the effects of KD on fat mass are consistent in all studies evaluating body composition during KD regimens on athletes [ 13 , 20 , 40 ], the same was not confirmed for lean mass, with some authors showing a catabolic effect of KD on muscle [ 19 , 41 , 42 , 43 ], others showing no direct effects [ 13 , 44 ]. Only one study showed a higher increase in lean body mass that was measured after one week of carbohydrate recharge [ 45 ].…”
Section: Discussionmentioning
confidence: 96%
“…While the effects of KD on fat mass are consistent in all studies evaluating body composition during KD regimens on athletes [ 13 , 20 , 40 ], the same was not confirmed for lean mass, with some authors showing a catabolic effect of KD on muscle [ 19 , 41 , 42 , 43 ], others showing no direct effects [ 13 , 44 ]. Only one study showed a higher increase in lean body mass that was measured after one week of carbohydrate recharge [ 45 ].…”
Section: Discussionmentioning
confidence: 96%
“…It affects physical health and has positive effects on fat oxidation but shows conflicting results regarding the effects of a KD on performance, which are mostly shown in the long term. Thus, there are both beneficial and detrimental effects after using a KD strategy in athletic populations [ 10 , 51 , 52 , 53 ]. Further research is required to establish recommended protocols regarding a KD for athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is required to establish recommended protocols regarding a KD for athletes. Furthermore, deleterious effects on stool microbiota and iron metabolism have been shown [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since there are still many concerns about using the Ketogenic diet in athletics, certain successful research on the Ketogenic diet and performance illustrates the necessity for a complete examination of its modes of action for sporting purposes (Bowler & Polman, 2020).…”
Section: The Influence Of a Ketogenic Diet On Endurance And Maximal I...mentioning
confidence: 99%